2021
DOI: 10.3389/fped.2021.667362
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Movement Behaviors and Emotional Changes in Toddlers and Preschoolers During Early Stages of the COVID-19 Pandemic in Chile

Abstract: Background: There is limited evidence about emotional and behavioral responses in toddlers and preschoolers during the novel coronavirus (COVID-19) pandemic, particularly in Latin America.Objective: To assess associations between changes in movement behaviors (physical activity, screen time and sleeping) and emotional changes in toddlers and preschoolers during early stages of the pandemic in Chile.Methods: A cross-sectional study conducted from March 30th to April 27th, 2020. Main caregivers of 1- to 5-year-o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…For older children, behavioral symptoms reported included clinginess, distraction, irritability, and fear of asking questions about the epidemic [22]. Other findings related to mood and emotional status included increases in being affectionate, restless, and frustrated [27]. The behavioral health of non-hospitalized children with COVID-19 had been reported by parents to have been worsening as the pandemic was progressing [42].…”
Section: Long-term Effects On Social and Behavioral Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…For older children, behavioral symptoms reported included clinginess, distraction, irritability, and fear of asking questions about the epidemic [22]. Other findings related to mood and emotional status included increases in being affectionate, restless, and frustrated [27]. The behavioral health of non-hospitalized children with COVID-19 had been reported by parents to have been worsening as the pandemic was progressing [42].…”
Section: Long-term Effects On Social and Behavioral Healthmentioning
confidence: 99%
“…Preliminary reports in the U.S. point consistently to disparities by race and ethnicity, with African Americans, Hispanics/Latinos, American Indians/Alaska Natives, and Native Hawaiians/ Other Pacific Islanders experiencing a greater COVID-19 burden than non-Hispanic White populations [26]. Reports by geographic locations indicate that cases are substantially greater in economically disadvantaged census tracts [1,27]. These long-term effects, even if only mild in severity, can have a detrimental impact on a person's overall quality of life [28].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the odds for children to have mental health problems increased by at least 40% from high-income to low-income (Li et al, 2021). One study in Chile found that children aged 1-5 years old were more restless and frustrated during the pandemic time compared to prepandemic time (Aguilar-Farias et al, 2021). Similarly, another study reported an increase in crying, sadness, and being upset among preschoolers (Schmidt et al, 2021).…”
Section: Pandemic-related Mental Health Crisis In Children From Low-i...mentioning
confidence: 99%
“…To mitigate the spread and infection, governments from around the world have adopted measures to limit social contact, including stay-at-home orders [ 3 ], travel restrictions, and school closures [ 4 ]; upon reopening, both the schools and their students and families have had to adapt to a new pandemic reality [ 4 , 5 ]. These extraordinary arrangements have had negative social, emotional, and physical impacts on young children, including sleeping disorders, reduced physical activity (PA), and increased sedentary behaviour (SB) [ 6 , 7 , 8 , 9 ]. When space to play has been provided, the increased SB and decreased PA in toddlers have been attenuated [ 10 ].…”
Section: Introductionmentioning
confidence: 99%